2014
DOI: 10.1016/j.ajo.2014.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Success With Single-Agent Immunosuppression for Multifocal Choroidopathies

Abstract: Purpose To evaluate the success of single-agent immunosuppression for patients with the posterior uveitides, birdshot chorioretinitis, multifocal choroiditis with panuveitis, and punctate inner choroiditis. Design Retrospective case series. Methods Setting: Tertiary care uveitis practices. Population: Patients initiated on immunomodulatory therapy. Intervention: Patients were treated with prednisone 1 mg/kg and mycophenolate 2 gm daily. Prednisone was tapered after one month. Immunosuppression was escalate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…When corticosteroid therapy does not have the desired effect, immunomodulatory agents represent the next category of medication used. This includes the broad categories of antimetabolites (azathioprine, methotrexate, and mycophenolate mofetil), alkylating agents (cyclophosphamide, chlorambucil), T-cell inhibitors (cyclosporine, tacrolimus) and cytokines (interferon alpha) [ 1 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…When corticosteroid therapy does not have the desired effect, immunomodulatory agents represent the next category of medication used. This includes the broad categories of antimetabolites (azathioprine, methotrexate, and mycophenolate mofetil), alkylating agents (cyclophosphamide, chlorambucil), T-cell inhibitors (cyclosporine, tacrolimus) and cytokines (interferon alpha) [ 1 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, modified diabetic retinopathy study (DRS) visual field scores were obtained using GVF by calculating the sum of degrees seen along each 30° meridian using I4e and IV41 objects. Using the above method of calculation, a gain of >20° in the visual field was found to occur with immunomodulatory therapy in patients with BSCR [ 10 , 25 ]. Thus, GVF testing appears to be an efficient objective measure for assessment of vision-related functional loss in patients with BSCR.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 Despite the success with 2 g/d mycophenolate in the SITE study, 2-year follow-up in the Mount Sinai study of posterior uveitides suggested that approximately 75% of patients treated with mycophenolate would require 3 g/day to experience successful corticosteroid sparing. 4 More modern approaches often either initiate methotrexate at 15 mg/week and escalate to 25 mg/week in a single step if the lower dose is not adequately effective or use 25 mg/week; similarly, mycophenolate is administered at 2 g/day and increased to 3 g/day in a single step if the lower dose is not adequately effective or to just increased automatically to 3 g/day. 1 In this context, the First-Line Antimetabolites for Steroidsparing Treatment (FAST) research group conducted a randomized clinical trial of methotrexate vs mycophenolate as the single immunosuppressive agent for treating noninfectious intermediate, posterior, and panuveitides, the results of which are reported in this issue of JAMA.…”
Section: Main Outcomes and Measuresmentioning
confidence: 99%